2022
DOI: 10.3390/ijerph192416845
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Strategies: Moderating the Relationship between Executive Functions and Daily Functioning

Abstract: Whereas prior studies have addressed relationships between cognitive strategies and learning and achievement, very few dealt with their connection to daily functioning. This study examines the moderation effect of the frequency of compensatory cognitive strategy use within that relationship among university students. A sample of 336 students (18–36 years; 180 women, 156 men) answered the Dysexecutive Questionnaire (DEX; executive function components), Time Organization and Participation Scale (TOPS; daily func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 59 publications
(71 reference statements)
0
1
0
1
Order By: Relevance
“…Scientific and academic discourse transforms in line with the emergence of new tools for argumentation, negotiation, publication writing, etc. In these circumstances, Fogel (2022) believes that digital technologies can become effective assistants in presenting a clear standpoint of the researcher and improve the ability to conduct constructive scientific discourse. The development of digital technologies and specialised software directly impacts the linguistic formation and dynamic trends of cognitive-communicative strategies in English.…”
Section: Discussionmentioning
confidence: 99%
“…Scientific and academic discourse transforms in line with the emergence of new tools for argumentation, negotiation, publication writing, etc. In these circumstances, Fogel (2022) believes that digital technologies can become effective assistants in presenting a clear standpoint of the researcher and improve the ability to conduct constructive scientific discourse. The development of digital technologies and specialised software directly impacts the linguistic formation and dynamic trends of cognitive-communicative strategies in English.…”
Section: Discussionmentioning
confidence: 99%
“…In the same vein, previous studies have also identified lower use of cognitive strategies such as self-checking and pausing and re-reading during WCPA completion as important indicators of self-monitoring deficits in stroke patients (Jaywant et al, 2022 ) and in an older patients population (Arora et al, 2021 ). Additionally, several studies (Villalobos et al, 2020 ; Fogel, 2022 ) have considered the use of strategies and metacognition (i.e. self-awareness) as factors capable of modulating the typical relationship between ADL and EF.…”
Section: Discussionmentioning
confidence: 99%
“…ДЛПФК играет критическую роль в реализации регуляторных функций (executive functions), благодаря которым становятся возможными планирование, контроль и регуляция собственного поведения [6]. Сохранность регуляторных функций важна для успешного выполнения повседневных задач [7], профессионального [8] и социального [9] функционирования.…”
Section: Introductionunclassified